Solution of the problem of calculating the leakage working fluid in eccentric gap of the ball piston pair hydraulic fluid power machine - Samorodov, Vadym; Avrunin, Grigory (Національний технічний університет "Харківський політехнічний інститут", 2021)
Goal. Conclusion of an analytical expression for calculating leaks in the gap between the ball-pistons and cylindrical holes in the cylinder blocks of radial-piston hydraulic pumps and hydraulic motors of hydraulic fluid power transmission. The object of study was the hydraulic fluid power transmission of the GOP-900 model in a monoblock design, consisting of a pump with an adjustable displacement and an hydraulic motor with a constant displacement. Method. For the laminar flow of the working fluid in the gap between the ball-piston and the cylinder, a calculation scheme is developed and a corresponding mathematical model is proposed for calculating the flow differential in each of the sections along the forming hole in the cylinder block of the hydraulic machine, followed by the integration of the specified differential. The calculation of the working fluid leaks in the MathCAD-15 medium allowed us to determine the average values of leaks with a concentric and eccentric arrangement of the piston balls in the holes of the cylinder blocks for specific set values for the diameters of the piston balls, the viscosity of the working fluid and the pressure drop between the discharge and discharge cavities. Results. For the first time аnalytical expressions are obtained that allow calculating leaks in the gap between the ball-piston and the hole in the cylinder block of a radial-piston hydraulic machine. The adequacy of the mathematical model is confirmed by the results of comparisons with the data of experimental measurements of working fluid leaks. It is shown that the coefficient of eccentricity of the circular gap used in the calculations using the Hagen-Poiseuille formula with a value of 2,5 is significantly overestimated. Conclusion. The method of calculating working fluid leaks in ball-piston hydraulic machines is recommended for use by specialists when developing new hydraulic machines and conducting diagnostics of the technical condition of those in operation in order to determine the volumetric efficiency and, in particular, its effect on the speed of vehicles whose transmissions use hydraulic machines with ball-pistons.

Мета. Висновок аналітичного виразу для розрахунку витоків в зазорі між шариками-поршнями і циліндричними отворами в блоках циліндрів радіальнопоршевих гідромашин – насосів і гідромоторів об'ємних гідропередач. Об'єктом вивчення стала об'ємна гідропередача моделі ГОП-900 в моноблочному виконанні, що складається з насоса з регульованим робочим об'ємом і гідромотора з постійним робочим об'ємом. Метод. Для ламінарної течії робочої рідини в зазорі між шариком-поршнем і циліндром розроблена розрахункова схема і запропонована відповідна математичної модель для обчислення диференціала витрати в кожному з перетинів уздовж отвору в блоці циліндрів гідромашини з подальшим інтегруванням вказаного диференціала. Розрахунок витоків робочої рідини в середовищі MathCAD-15 дозволив визначити середні значення витоків при концентричному і ексцентричному розташуванні шариків-поршнів в отворах блоків циліндрів для конкретних заданих значень по діаметрам шариків-поршнів, в'язкості робочої рідини і перепаду тиску між нагнітальною і зливною порожнинами. Результати. Вперше отримані аналітичні вирази, що дозволяють провести розрахунок витоків в зазорі між шариком-поршнем і отвором в блоці циліндрів радіальнопоршневої гідромашини. Підтверджено адекватність математичної моделі за результатами порівнянь з даними експериментальних вимірювань витоків робочої рідини. Показано, що використовуваний при розрахунках за формулою Гагена-Пуазейля коефіцієнт ексцентричності кругової щілини значенням в 2,5 є істотно завищеним. Укладення. Методика розрахунку витоків робочої рідини в шарикопоршневих гідромашинах рекомендується до використання фахівцями при розробці нових гідромашин і проведенні діагностики технічного стану тих, що знаходяться в експлуатації, з метою визначення об'ємного ККД і зокрема його впливу на швидкість транспортних засобів, в трансмісіях яких використовуються гідромашини з шариками-поршнями.
Рішення задачі розрахунку витоків робочої рідини в ексцентричному зазорі шарикопоршневої пари об'ємної гідромашини
Keywords: hydraulic transmissions; ball-piston; cylinder; mathematical model; гідропередачі; шарик-поршень; циліндр; математична модель